Phenotypic and genotypic characterisation of clinically relevant Staphylococcus aureus isolates from cystic fibrosis patients from private clinics in South Africa - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2024)
Dissertation (MSc (Medical Microbiology))--University of Pretoria, 2024.